Association Between Burnout and Intention to Emigrate in Peruvian health-care Workers - Anduaga-Beramendi, Alexander (2018)
Background: Emigration of health-care workers is a problem within global health systems which affects many countries, including Peru. Several factors have caused health-care workers to emigrate, including burnout syndrome (BS). This study aims to identify the association between BS and its dimensions with the intention of physicians and nurses to emigrate from Peru in 2014. Methods: A cross-sectional study, based on a secondary analysis of the National Survey of Health Users (ENSUSALUD - 2014) was conducted. Sampling was probabilistic, considering the 24 departments of Peru. We include the questionnaire for physicians and nurses, accounting for 5062 workers. BS was measured by the Maslach Burnout Inventory-Human Services Survey. Adjusted odds ratio (OR) was calculated using multiple logistic regression. Results: Of the study population, 44.1% were physicians, 37.7% males, and 23.1% were working in Lima. It was found that 2.8% [95% confidence interval (CI): 2.19–3.45] of health-care workers had BS. The overall prevalence of intention to emigrate among health-care workers was 7.4% (95% CI: 6.36–8.40). Association was found between BS and intention to emigrate in Peruvian health-care workers (OR = 2.15; 95% CI: 1.05–4.40). Emotional exhaustion was the BS dimension most associated with intention to emigrate (OR = 1.80; 95% CI: 1.16–2.78). Conclusion: Physicians and nurses from Peru who suffered from BS were more likely to have intention to emigrate. Policies should be established to reduce BS as a strategy to control “brain drain” from health-care workers of Peru.